2002
DOI: 10.1016/s0896-6273(02)00613-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution of a Decision-Making Process in Medial Premotor Cortex

Abstract: The events linking sensory discrimination to motor action remain unclear. It is not known, for example, whether the motor areas of the frontal lobe receive the result of the discrimination process from other areas or whether they actively participate in it. To investigate this, we trained monkeys to discriminate between two mechanical vibrations applied sequentially to the fingertips; here subjects had to recall the first vibration, compare it to the second one, and indicate with a hand/arm movement which of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
197
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(215 citation statements)
references
References 57 publications
18
197
0
Order By: Relevance
“…During a vibrotactile discrimination experiment, single-unit recordings in somatosensory cortex predicted whether monkeys could perceive a difference in the stimulation frequency (Salinas et al, 2000). In the same kind of tasks, Romo et al (Romo et al, 2003) demonstrated the role of medial prefrontal and premotor cortices in forming the decision initially driven by evidence in somatosensory areas (see also de Lafuente and Romo, 2005;Hernandez et al, 2002). The same pattern of sequential stages has been repeatedly shown in the visual domain.…”
Section: Introductionmentioning
confidence: 80%
“…During a vibrotactile discrimination experiment, single-unit recordings in somatosensory cortex predicted whether monkeys could perceive a difference in the stimulation frequency (Salinas et al, 2000). In the same kind of tasks, Romo et al (Romo et al, 2003) demonstrated the role of medial prefrontal and premotor cortices in forming the decision initially driven by evidence in somatosensory areas (see also de Lafuente and Romo, 2005;Hernandez et al, 2002). The same pattern of sequential stages has been repeatedly shown in the visual domain.…”
Section: Introductionmentioning
confidence: 80%
“…We found that the activity of the recorded neurons of several cortical areas encodes f1 in a monotonic firing rate code beginning in the primary somatosensory cortex (5-7), continuing in the secondary somatosensory cortex (5), the ventral premotor cortex (19), the prefrontal cortex (10), and the medial premotor cortex (MPc) (18). Except for the primary somatosensory cortex, these cortical areas encode information of f1 during the delay period between f1 and f2 (5,10,11,(17)(18)(19). During presentation of f2, some neurons of all these cortical areas respond to f2, but some other neurons reflect past information of f1, or of the difference between f2 and f1, and generate a differential response consistent with the decision motor report (17)(18)(19).…”
mentioning
confidence: 99%
“…But what is stored in the memory circuits, the final decision itself or the sensory information on which the decision is based? We investigated this question by recording from single neurons in MPc (the presupplementary motor area and the supplementary motor area proper), an area involved in decision making and motor choice (18,(23)(24)(25), while trained monkeys discriminated the difference in frequency between consecutive vibrotactile stimuli, f1 and f2. Crucially, monkeys were asked to report discrimination after a fixed delay period between the end of f2 and a cue that triggered the beginning of the motor report.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TMS did not affect performance if delivered to the ipsilateral SI at any time point. The researchers proposed that the tactile memory trace was held initially for a certain period of time in both SI and SII, but later it would be held in higher level of cortex, such as the premotor and prefrontal cortex (Romo et al, 1999;Brody et al, 2003;Passingham and Sakai, 2004;Romo et al, 2004;Hernandez et al, 2002). A similar conclusion was drawn by a recent human fMRI study on haptic working memory (Kaas et al, 2007).…”
Section: Introductionmentioning
confidence: 86%